Examining the Professionalization of English Language Teaching (ELT): From a Global Perspective - Alam, Md. Tariqul; Goyal, Aditi (Progress in Language, Literature and Education Research Vol. 6, 2024)
The public education system was established in the 19th century to ensure that everyone could read and write. In the past, parents would often teach their children at home, but as society became more industrialized, teachers were needed to fill this role. Traditionally, new teachers would learn from experienced teachers in a sort of apprenticeship. Teacher training courses were also available in the main towns. Today, most teacher training programs are still offered by "normal schools," which are secondary schools that accept students at around 15 years old for a two- or three-year program. These schools are found all over the world, but there are many in Latin America. In Europe and North America, teaching colleges have been replaced by universities. By the early 20th century, the teaching profession had become more formalized, with official training and certification requirements. Today, it is important to professionalize English teaching globally to improve communication. This research paper aims to explain the importance of professionalizing English language instruction in a global setting.